ENGLISH LANGUAGE DOMINANCE AND ITS IMPACT ON SEPEDI ORAL PROFICIENCY: A CASE STUDY OF GRADE 11 LEARNERS IN SOUTH AFRICA - Morokwe Piet Matlebjane; Phaswane Phillip Phokwane; Ngwanamphaga Alettah Matji (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study investigates the effects of English as the Language of Learning and Teaching (LOLT) on the oral proficiency of Grade 11 Sepedi Home Language learners in South Africa. Situated within sociocultural and multilingual education perspectives, the study explores how the dominance of English influences learners’ use of Sepedi, pronunciation patterns, vocabulary use, and overall oral proficiency. A qualitative case study design was employed involving eight purposively selected Grade 11 learners. Data were collected through open-ended questionnaires and oral assessment tasks and analyzed using deductive thematic analysis. The findings indicate that the dominance of English reduces opportunities for meaningful use of Sepedi in academic contexts, contributes to phonological transfer, and increases learners’ reliance on English vocabulary during communication. Participants also perceived English as significantly influencing their everyday use of Sepedi. These patterns suggest that sustained exposure to English as the dominant language of instruction may limit the development and maintenance of Sepedi oral proficiency. The study highlights the importance of additive multilingual educational practices that promote the meaningful use of both English and indigenous languages in schools. The findings contribute to ongoing discussions on multilingual education, language maintenance, and educational equity in South Africa.